The Distribution of Types of Aberrant Behavior in the Population of Young Men and Women - Paškota, Mira; Kron, Leposava; Hošek, Ankica; Momirović, Konstantin (Zbornik Instituta za kriminološka i sociološka istraživanja, 2005)
Random sample of 2664 subjects, age of 18, 1332 male and 1332 female, was described by 46 binary indicators of aberrant behavior and then classified by one taxonomic neural network that with coefficient of recognition of 0.999, found four very well defined taxons. As analysis of correspondence has shown, subjects of different sexes differed significantly on intensity and modality of aberrant behavior. In taxon of subjects with very low intensity of all modalities of aberrant behavior, something below average functions of cognitive processors, normal but astenicaly modulated functions of conative regulators and average level of socialization, there were 71.3% of female and only 28.7% of male subjects. On the contrary, in the taxon of primary aggressive subjects with very high intensity of aggressive modality of aberrant behavior but otherwise normal functions of cognitive processor and conative regulator, there were 88.2% of male, and only 11.8% of female subjects. The differences in other two taxons were far less, but still significant. In taxon of those who were prone to alcoholism but otherwise with week intensity of aberrant behavior, normal conative and something above average cognitive functions and average level of socialization, there were 57.2% of male and 42.8% of female subjects. In the taxon of subjects very badly adapted to school environment because of lower efficiency of conative regulators, in spite of normal functions of cognitive processor, there were 56,3% of male and 43.7% of female subjects. Therefore, the intensity of aberrant behavior was significantly higher at men of this age, and also the intensity of all modalities of behavior of that kind was also higher. Of all male subjects, only 24% didn't show any serious symptoms of aberrant behavior, and even 27.6% showed symptoms of, in essence, psychopathic behavior. On the contrary, from all female subjects, almost 60% didn't show any serious symptoms of aberrant behavior, and only 3.7% had symptoms of behavior that are characteristic for population of psychopath. Because of that, coefficient of separation of sexes was significant, but in essence, relations between belonging to taxons and sex weren't symmetrical: coefficient of belonging to taxon on the basis of subject's sex was 0.56, and coefficient of belonging to sex on the basis of belonging to certain taxon was 0.72, and that is not only significant, but also large difference. As this results were in concordance with results of former analysis on sexual dimorphism in criminological relevant space, some explicative hypothesis were suggested on the basis of previous researches on sexual dimorphism.